(untitled) (Studia Prawnicze / The Legal Studies, 1993)
Autor pokazuje, w oparciu o analizę spójnego i przemyślnego postępowania administracyjnego w zakresie ochrony środowiska, jakie wymogi wstępne prawo to stawia przed projektodawcami aktów legislacyjnych, w jaki sposób spaja ono działalność wszystkich urzędów państwowych w tej dziedzinie w jeden koherentny system oraz jak ważną rolę w tym systemie wyznacza się wykorzystaniu przez urzędy państwowe osiągnięć nauki, wreszcie jaką rolę prawo amerykańskie przywiązuje do wprzęgnięcia obywateli oraz ich organizacji społecznych i zawodowych w proces przygotowywania decyzji odnoszących się do środowiska naturalnego. On the basis of an analysis of the coherent and well thought-out administrative procedure in the field of environmental protection, the author shows the prerequisites this law places on the persons preparing drafts of legislative acts, how it binds the activities of all state authorities in this field into one coherent system, and how important is the role assigned in this system to the use of scientific achievements by state authorities, and finally, what is the role the US law foresees for involving citizens and their social and professional organisations in the preparation of decisions related to the environment.